ChemInform Abstract: An Efficient Method for Sterically Demanding Suzuki—Miyaura Coupling Reactions. Issue 30 (4th July 2013) - Zhao, Qing; Li, Chengxi; Senanayake, Chris H.; Tang, Wenjun
Abstract An efficient method for sterically demanding Suzuki—Miyaura coupling reactions is developed.